Atomic‐Scale Observation of Electrochemically Reversible Phase Transformations in SnSe2 Single Crystals. Issue 51 (25th October 2018) - Kim, Sungkyu; Yao, Zhenpeng; Lim, Jin‐Myoung; Hersam, Mark C.; Wolverton, Chris; Dravid, Vinayak P.; He, Kai
Abstract: 2D materials have shown great promise to advance next‐generation lithium‐ion battery technology. Specifically, tin‐based chalcogenides have attracted widespread attention because lithium insertion can introduce phase transformations via three types of reactions—intercalation, conversion, and alloying—but the corresponding structural changes throughout these processes, and whether they are reversible, are not fully understood. Here, the first real‐time and atomic‐scale observation of reversible phase transformations is reported during the lithiation and delithiation of SnSe2 single crystals, using in situ high‐resolution transmission electron microscopy complemented by first‐principles calculations. Lithiation proceeds sequentially through intercalation, conversion, and alloying reactions (SnSe2 → Li x SnSe2 → Li2 Se + Sn → Li2 Se + Li17 Sn4 ) in a manner that maintains structural and crystallographic integrity, whereas delithiation forms numerous well‐aligned SnSe2 nanodomains via a homogeneous deconversion process, but gradually loses the coherent orientation in subsequent cycling. Furthermore, alloying and dealloying reactions cause dramatic structural reorganization and thereby consequently reduce structural stability and electrochemical cyclability, which implies that deep discharge for Sn chalcogenide electrodes should be avoided. Overall, the findings elucidate atomistic lithiation and delithiation mechanisms in SnSe2 with potential implications for the broader class of 2D metal chalcogenides. Abstract : The electrochemically reversible phase transformations during lithiation and delithiation of SnSe2 single crystals are visualized atomically in real time using in situ high‐resolution transmission electron microscopy. Combined with density functional theory calculation, the atomic structures of the intermediate phases are identified and the reversible reaction mechanism is confirmed, which provides valuable implications to 2D metal chalcogenides as electrodes for lithium‐ion batteries.